1998
DOI: 10.1051/rnd:19980601
|View full text |Cite
|
Sign up to set email alerts
|

In vivo versus in vitro produced bovine ova: similarities and differences relevant for practical application

Abstract: -This present review describes some differences and similarities between bovine embryos produced in vivo and in vitro.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
30
0
1

Year Published

2000
2000
2008
2008

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 73 publications
(31 citation statements)
references
References 47 publications
0
30
0
1
Order By: Relevance
“…The identification of novel genes involved in blastocyst formation and the analysis of their expression patterns may help us to understand the mechanisms that control blastocyst formation and may help us to understand why certain embryos do not make it through this stage. As in vitro culture conditions do not fully mimic the in vivo situation and as it has been shown that morphological and physiological differences [5-7] as well as differences in gene expression [8-11] exist between in vivo and in vitro cultured embryos, the RNA expression levels of in vitro produced embryos should be compared with those of in vivo "golden standard" embryos. Changes in transcript abundance between in vitro and in vivo embryos may help to assess the normality of in vitro produced embryos and may help to optimise the in vitro culture conditions.…”
Section: Introductionmentioning
confidence: 99%
“…The identification of novel genes involved in blastocyst formation and the analysis of their expression patterns may help us to understand the mechanisms that control blastocyst formation and may help us to understand why certain embryos do not make it through this stage. As in vitro culture conditions do not fully mimic the in vivo situation and as it has been shown that morphological and physiological differences [5-7] as well as differences in gene expression [8-11] exist between in vivo and in vitro cultured embryos, the RNA expression levels of in vitro produced embryos should be compared with those of in vivo "golden standard" embryos. Changes in transcript abundance between in vitro and in vivo embryos may help to assess the normality of in vitro produced embryos and may help to optimise the in vitro culture conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Despite recent improvements in bovine in vitro production (IVP) systems, IVP embryos display marked differences compared with their in vivo counterparts (for reviews, see [6][7][8]. The in vitro culture system has profound effects on mRNA expression patterns of developmentally important genes [9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…Although significant progress has been made in assisted reproductive technology, during the last two decades multiple ovulations by gonadotrophin treatments still represents the greater source of embryos for all technologies connected to embryo transfer programs in domestic species [15].…”
Section: Introductionmentioning
confidence: 99%